2021
DOI: 10.1002/aqc.3554
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the distribution of priority benthic habitats through a remotely operated vehicle to support conservation measures off Linosa Island (Sicily Channel, Mediterranean Sea)

Abstract: 1. Explorations of the Mediterranean deep sea using remotely operated vehicles have shown that the sea bed hosts rich habitats, supporting high biodiversity.However, there have been only a few studies dealing with the southern part of the basin, leading to limited protection and conservation efforts in this area.2. This study aimed to explore the sea bed off Linosa Island (Sicily Channel, southern Mediterranean Sea), which is considered a 'sentinel area' for alien species and global environmental changes owing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 62 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…These formations play a crucial role in the welfare of the sea bottom as they act as an excellent feeding ground for many fishes and crustaceans and as a regulator of the carbon production in the sea (Martin et al, 2013). While many studies are dedicated to different species of corals found around the Mediterranean (Ballesteros, 2006;Blondel et al, 2006;Bartlett et al, 2009;Bonacorsi et al, 2012;Giakoumi et al, 2013;Martin et al, 2014;Ingrassia et al, 2019;Romagnoli et al, 2021;Pierdomenico et al, 2021;De Falco et al, 2022), only a few take note of the unique coralligenous formations found throughout the Aegean Sea, especially in the Cyclades archipelago. There is only one systematic study (Georgiadis et al, 2009) dedicated to the research and mapping of this unique east Mediterranean habitat.…”
Section: Introductionmentioning
confidence: 99%
“…These formations play a crucial role in the welfare of the sea bottom as they act as an excellent feeding ground for many fishes and crustaceans and as a regulator of the carbon production in the sea (Martin et al, 2013). While many studies are dedicated to different species of corals found around the Mediterranean (Ballesteros, 2006;Blondel et al, 2006;Bartlett et al, 2009;Bonacorsi et al, 2012;Giakoumi et al, 2013;Martin et al, 2014;Ingrassia et al, 2019;Romagnoli et al, 2021;Pierdomenico et al, 2021;De Falco et al, 2022), only a few take note of the unique coralligenous formations found throughout the Aegean Sea, especially in the Cyclades archipelago. There is only one systematic study (Georgiadis et al, 2009) dedicated to the research and mapping of this unique east Mediterranean habitat.…”
Section: Introductionmentioning
confidence: 99%
“…shell fragments or rocks). They are distributed worldwide and can be found at tropical (Amado‐Filho et al, 2012; Costa et al, 2020; Moura et al, 2021), temperate (Foster et al, 1997; Steller et al, 2003; Hinojosa‐Arango & Riosmena‐Rodríguez, 2004; García et al, 2014; Bracchi et al, 2019; Bracchi et al, 2022; Chimienti et al, 2020; Longo et al, 2020; Rendina et al, 2020; Romagnoli et al, 2021), and polar (Konar, Riosmena‐Rodriguez & Iken, 2006; Teichert et al, 2014; Ward et al, 2021) latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…In the Mediterranean, the distribution and conservation status of rhodolith beds are still poorly known, hindering the implementation of adequate conservation plans, although advances have been made in some locations (e.g., Barberá et al, 2012; Maggio et al, 2022; Romagnoli et al, 2021; Sciberras et al, 2009). In this context, identifying and monitoring rhodolith beds that are in good ecological condition is urgent.…”
Section: Introductionmentioning
confidence: 99%